2006
DOI: 10.1063/1.2400236
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative electron attachment to gas phase valine: A combined experimental and theoretical study

Abstract: Using a crossed electron/molecule beam technique the dissociative electron attachment (DEA) to gas phase L-valine, (CH(3))(2)CHCH(NH(2))COOH, is studied by means of mass spectrometric detection of the product anions. Additionally, ab initio calculations of the structures and energies of the anions and neutral fragments have been carried out at G2MP2 and B3LYP levels. Valine and the previously studied aliphatic amino acids glycine and alanine exhibit several common features due to the fact that at low electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
71
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 26 publications
6
71
0
1
Order By: Relevance
“…In cation formation at an electron energy of about 70 eV (close to the maximum of the ionization cross section) the molecular ion intensity is less than 1% of the intensity of the most abundant fragment ion formed by the loss of the neutral carboxyl group [10]. In the case of resonant anion formation the un-fragmented molecular anion cannot be observed at all [9,14,15]. Instead, the dehydrogenated parent anion is formed as the most abundant anion with the main resonance at the electron energy of 1.2 eV and other fragment anions can be observed at higher electron energies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cation formation at an electron energy of about 70 eV (close to the maximum of the ionization cross section) the molecular ion intensity is less than 1% of the intensity of the most abundant fragment ion formed by the loss of the neutral carboxyl group [10]. In the case of resonant anion formation the un-fragmented molecular anion cannot be observed at all [9,14,15]. Instead, the dehydrogenated parent anion is formed as the most abundant anion with the main resonance at the electron energy of 1.2 eV and other fragment anions can be observed at higher electron energies.…”
Section: Introductionmentioning
confidence: 99%
“…Valine is important in the biosynthesis of proteins in humans who acquire valine through their diet. Previous gas-phase studies with isolated valine have provided valuable insight into the stability of this molecule against dissociation by particle collisions [7][8][9][10][11][12][13][14][15]. Low-energy electron interactions with Contribution to the Topical Issue "Advances in Positron and Electron Scattering", edited by Paulo Limao-Vieira, Gustavo Garcia, E. Krishnakumar, James Sullivan, Hajime Tanuma and Zoran Petrovic.…”
Section: Introductionmentioning
confidence: 99%
“…Notable examples of such processes include the formation of CN À from hexafluoroacetone azine [9] and the amino acids valine [10] and glycine [11] as well as multiple fragmentation processes observed close to 0 eV in DEA to the well known explosive TNT [12]. Other examples include those described in DEA studies of trifluoroacetic acid [13] and pentafluorophenylacetonitrile [14].…”
Section: Introductionmentioning
confidence: 99%
“…This is only possible through rearrangement and the formation of new chemical bonds. The first reported example of such a process was from DEA experiments to gas phase valine [1]. There, the authors reported the formation of CN − brought about by the formation of neutral H 2 and a C−H bond to form n-propane.…”
mentioning
confidence: 99%
“…In the field of dissociative electron attachment (DEA) several reports show the existence of a close to zero eV dissociative channel leading to the rupture of two or more chemical bonds and rearrangement of the fragments [1,2,3]. The energy required to drive these reactions is quite high compared to the electron affinity of the charge carrying moiety and yet this process has been observed to occur with high cross sections.…”
mentioning
confidence: 99%